School Strategies to Increase Work Opportunities Graduated from SMK Tamansiswa Mojoagung - Setiawan*, Agus; Riyanto, Yatim; Handayaningrum, Warih (Universitas Syiah Kuala, 2023)
The purpose of this research is to describe the strategy of Public Vocational High School Tamansiswa Mojoagung to improve the employment opportunities of graduates, the efforts of school is in cooperation with the graduates, the supporting and obstacle factor, and the role of management in improving employment opportunities of graduates. This research used the qualitative approach that was implemented through a case study. Data were collected using interview, observation and documentation.The result showsthat school strategy or increasing the opportunity of hiring job is having good relation with DU/DI through BKK in conducting the internship. School effort in making good relation with school alumnus is setting an Alufika group and graduation book.there are supported and unsupporting factor along with management roles for rising the opportunity of school alumnus, they are representive of public relations, human resources development, and curriculum.